The utility of diffusion-weighted imaging for differentiation of phyllodes tumor from fibroadenoma and breast cancer - Fang, Jinzhi; Zhang, Yuzhong; Li, Ruifeng; Liang, Lanlan; Yu, Juan; Hu, Ziqi; Zhou, Lingling; Liu, Renwei (Frontiers in Oncology, 2023)
Objective To evaluate the utility of apparent diffusion coefficient (ADC) values for differentiating breast tumors. Methods The medical records of 17 patients with phyllodes tumor [PT; circular regions of interest (ROI-cs) n = 171], 74 patients with fibroadenomas (FAs; ROI-cs, n = 94), and 57 patients with breast cancers (BCs; ROI-cs, n = 104) confirmed by surgical pathology were retrospectively reviewed. Results There were significant differences between PTs, FAs, and BCs in ADCmean, ADCmax, and ADCmin values. The cutoff ADCmean for differentiating PTs from FAs was 1.435 × 10−3 mm2/s, PTs from BCs was 1.100 × 10−3 mm2/s, and FAs from BCs was 0.925 × 10−3 mm2/s. There were significant differences between benign PTs, borderline PTs, and malignant PTs in ADCmean, ADCmax, and ADCmin values. The cutoff ADCmean for differentiating benign PTs from borderline PTs was 1.215 × 10−3 mm2/s, and borderline PTs from malignant PTs was 1.665 × 10−3 mm2/s. Conclusion DWI provides quantitative information that can help distinguish breast tumors.